al-Qiyam al-Syakhshiyyah wa Tanfidzuha fi Ta’lim al-Lughah al-Arabiyyah - Muhammad Jafar Shodiq (Jurnal Alsinatuna, 2018)
The background of this research is the poor condition of young generations from the values of character and culture. School as an educational institution has the responsibility to establish and develop the character of students. This paper aims to determine the role of learning Arabic in character education, character education applications in learning the Arabic language and what the values can be internalized in the Arabic language learning.